miR-559 Inhibits Proliferation, Autophagy, and Angiogenesis of Hepatocellular Carcinoma Cells by Targeting PARD3 - Chunjing Wang; Chengcheng Li; Rui Hao (Mediators of Inflammation)
Hepatocellular carcinoma (HCC) is one of the most common cancers in the world and has a high mortality rate. Although prevention and treatment of HCC has improved, it still faces poor prognosis and high mortality. miRNAs play a critical role in the tumorigenesis of HCC, but the underlying mechanism has not been well investigated. Here, the functions and interaction between miR-559 and PARD3 were investigated in HCC cells. Increased PARD3 and decreased miR-559 expression were observed in HCC cells compared with those in normal liver cells, especially in Huh-7 cells. Studies further demonstrated that PARD3 silencing or miR-559 overexpression impaired the proliferation, autophagy, and angiogenesis in Huh-7 cells. Mechanistically, PARD3 represents a target of miR-559. Furthermore, investigations revealed that miR-559 inhibition induced the expression of PARD3, thereby enhancing cell proliferation, autophagy, and angiogenesis in Huh-7 cells. These results reveal the interaction between miR-559 and PARD3 in HCC cells and provide new insights into their potential targets as therapeutic treatment against HCC.